Three African religious founders - Bengtson, Dale R. (Journal of Religion in Africa, 1975)
The article challenges the anthropological category of culture hero in the study of African traditional religions. Obscured within this classification are sacred beings who are sui generis–religious founders who give form to the various traditions by establishing cults, secret societies, sacred places, etc. Following a discussion of the nature of culture heroes and founders, a distinction is made between transitive founders (with an emphasis on foundation [aition] the founder's sacred character has yet to be proven) and intransitive founders (with an emphasis on the person [phē] of the founder, around which a new cult is established). Founders, their meanings and functions, are then discussed in three African traditions–Nupe, Shilluk, Nama Hottentot. The conclusion suggests that the category of founder has implications for a new perspective on the "problem" of the high god and the nature of African communities.
free
Keywords: Africa – Religion; Cultus; African; God (African religion); Mythology; African; Nama (African people); Nupe (African people); Shilluks (African people)